2014
DOI: 10.4314/njt.v33i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Polyvinyl Waste Powder as Partial Replacement for Cement in Concrete Production

Abstract: This work presents the results of investigation This work presents the results of investigation This work presents the results of investigation This work presents the results of investigation as partial replacement of cement in the production of concrete

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Therefore, in the ever increasing efforts in converting waste to wealth, bagasse ash could be used as a supplement or partial replacement for cement in order to reduce the cement content requirement which ultimately reduces the cost of construction and maintenance of roads. Some researchers have attempted to examine the behaviours of soils with pozzolanic materials [6] and [7] while others when treated with bagasse ash. However, the chemistry and attributes behind its usefulness in soil stabilization had not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the ever increasing efforts in converting waste to wealth, bagasse ash could be used as a supplement or partial replacement for cement in order to reduce the cement content requirement which ultimately reduces the cost of construction and maintenance of roads. Some researchers have attempted to examine the behaviours of soils with pozzolanic materials [6] and [7] while others when treated with bagasse ash. However, the chemistry and attributes behind its usefulness in soil stabilization had not been shown.…”
Section: Introductionmentioning
confidence: 99%
“…However, 5 % SAMC content in the mix was considered as optimalum for an improved structural performance when compared with normal concrete. Ikponmwosa et al [11], presented a study on the suitability of polyvinyl waste powder as a partial replacement for cement in concrete production. As part of their findings, polyvinyl waste powder has a pozzolanic effect, served as a retarder, reduced workability and higher structural strength up to a 20 % replacement.…”
Section: No /mentioning
confidence: 99%
“…As part of their findings, polyvinyl waste powder has a pozzolanic effect, served as a retarder, reduced workability and higher structural strength up to a 20 % replacement. Reddy et al [12], studied the utilization of sugarcane bagasse ash in concrete by a partial replacement of cement. The results showed that the performance of concrete having up to a 10 % SCBA replacement met the requirements of BS 8110 [13] and can be used for the production of concrete for structural works.…”
Section: No /mentioning
confidence: 99%